Francisco de Goya and the art of critique - Cascardi, Anthony J., 1953- (Zone Books, 2022)
"The subject of this book is the relationship between the enormous, extraordinary, and sometimes baffling body of Goya's work, and the interconnected issues of modernity, in art, the Enlightenment, and the project of critique"--